A General Strategy to Design Highly Fluorogenic Far‐Red and Near‐Infrared Tetrazine Bioorthogonal Probes. Issue 5 (1st December 2020) - Mao, Wuyu; Tang, Jie; Dai, Liqun; He, Xinyu; Li, Jie; Cai, Larry; Liao, Ping; Jiang, Ruotian; Zhou, Jingwei; Wu, Haoxing
Abstract: Highly fluorogenic tetrazine bioorthogonal probes emitting at near‐infrared wavelengths are in strong demand for biomedical imaging applications. Herein, we have developed a strategy for forming a palette of novel Huaxi‐Fluor probes in situ, whose fluorescence increases hundreds of times upon forming the bioorthogonal reaction product, pyridazine. The resulting probes show large Stokes shifts and high quantum yields. Manipulating the conjugate length and pull–push strength in the fluorophore skeleton allows the emission wavelength to be fine‐tuned from 556 to 728 nm. The highly photo‐stable and biocompatible probes are suitable for visualizing organelles in live cells without a washing step and for imaging of tumors in live small animals to depths of 500 μm by two‐photon excitation. Abstract : A palette of highly fluorogenic Huaxi‐Fluor probes are turned on by a tetrazine bioorthogonal reaction. The emission wavelengths are fine‐tuned from the far‐red to near‐infrared. These highly stable and biocompatible probes are suitable for visualizing organelles in live cells without a washing step and for imaging of tumors in live small animals to depths of 500 μm by two‐photon excitation.